(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The prostate is a gland that covers the necks of the bladder in men and aids in ejaculation during sexual activity as well as the storage of some seminal fluid. The three most prevalent conditions affecting prostates are inflammation, benign enlargement, and prostate cancer.180 participants were enlisted to detect two SNPs (rs1058587 and rs1054564) by using the tetra-arm approach in the promoter of the GDF15 gene, then estimate the serum level of GDF15 protein by sandwich ELISA to investigate its relationship with disease severity. Variation of frequency distributions of genotypes and alleles among groups showed a positive association with the serum level of GDF15 protein as a relative risk factor. The study reflects a relationship between the variation in the expression of the two SNPs in the promoter and the serum level of protein, thus it can be considered as an indicator to measure the progression of prostates disease.